2014
DOI: 10.1590/s2175-78602014000200001
|View full text |Cite
|
Sign up to set email alerts
|

Flora vascular da Reserva Biológica da Represa do Grama, Minas Gerais, e sua relação florística com outras florestas do sudeste brasileiro

Abstract: ResumoEste trabalho apresenta o levantamento florístico das plantas vasculares da Reserva Biológica da Represa do Grama, um remanescente de floresta estacional semidecidual do Domínio Atlântico, situado no município de Descoberto, Minas Gerais. Foram realizadas coletas quinzenais de material fértil entre agosto de 1999 e dezembro de 2004. Além do levantamento, fez-se a comparação da composição florística através de análises multivariadas de agrupamento com outras nove áreas (3 de floresta estacional e 6 de omb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
(33 reference statements)
1
17
0
5
Order By: Relevance
“…Furthermore, it appears that dispersal limits can be a determining factor for the distribution of this group in the Brazilian Atlantic Forest, where closer areas show higher similarity, even when under environmental conditions showing discrepancy. This may be related to the capacity of the family to adapt to different habitats, exemplified by the ability to occupy different forest layers, where the same species can be found epiphytically, terricolously and rupicolously (Benzing, ; Forzza et al ., ). Meanwhile, for Piperaceae, floristic composition shows a stronger relation to environmental conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, it appears that dispersal limits can be a determining factor for the distribution of this group in the Brazilian Atlantic Forest, where closer areas show higher similarity, even when under environmental conditions showing discrepancy. This may be related to the capacity of the family to adapt to different habitats, exemplified by the ability to occupy different forest layers, where the same species can be found epiphytically, terricolously and rupicolously (Benzing, ; Forzza et al ., ). Meanwhile, for Piperaceae, floristic composition shows a stronger relation to environmental conditions.…”
Section: Discussionmentioning
confidence: 97%
“…This result was also found by Forzza et al . (), in a comparison between epiphytes from some areas of Atlantic Forest, in which 24 of the 41 registered species were shared between SSF and DEF. Concerning the woody component, SSF is also composed of DEF species more adapted to seasonality (Oliveira‐Filho & Fontes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Group A was composed of two areas whose distance to the ocean varied from 60 km ("spcuaso") to 165 km ("mgrbrg"), isolating it from group B (whose area with the closest proximity to the ocean was about 250 km away from it), located in the transition with the Cerrado. Forzza et al (2014) found a similar gradient when comparing the vascular flora of the Reserva Biológica da Represa do Grama ("mgrbrg") with nine other areas of the southeastern region of Brazil, with strong segregation between littoral and inland areas.…”
Section: Rhipsalis Cereusculamentioning
confidence: 71%
“…Although the areas of Minas Gerais are composed of SSF, the influence of dense ombrophilous forest has been noted by Barbosa et al (2014) in "mgfs" and by Forzza et al (2014) in "mgrbrg". Pifano et al (2007) also noticed such influence on the composition of the phanerogamic flora of Morro do Imperador, an area about 4 km from MK, and stated that milder temperatures of the region and geographic proximity to the littoral could be responsible for this relationship.…”
Section: Rhipsalis Cereusculamentioning
confidence: 96%
“…Bromeliaceae and Orchidaceae especially noteworthy for their high richness and endemism. Local floristic surveys along the Atlantic Forest demonstrate that these families figure among the richest in distinct areas of this domain, but in different proportions depending on, for example, altitude, latitude, and vegetation type (Barros et al 1991;Alves-Araújo et al 2008;Amorim et al 2008Amorim et al , 2009Scheer and Kinoshita 2009;Coelho and Amorim 2014;Forzza et al 2014;Landim et al 2015).…”
Section: Introductionmentioning
confidence: 99%